2019
DOI: 10.31703/gssr.2019(iv-i).31
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effects of the Official Development Assistance on GDP Per Capita in Pakistan

Abstract: The paper investigates the influence of official development support on Pakistan GDP per capita making use of time series yearly data from 1991 to 1917. ADF has been used for examining the level of integration of the data. After that, ARDL has been used for discovering the short and long-run relationship of the official development assistance and the GDP per capita. The results uncover that official assistance relationship with GDP per capita became negative in the short run in addition to a long-run period. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In her book titled, "Dead aid" she argues that foreign aid does not progress economic growth, but instead tends to promote rentseeking and on many occasions, serves the interest of the elite instead of the overall economy (Moyo, 2009). Synchronously to the assertion of Moyo, a study by Tariq, and Ali, (2019), found a negative relationship between official development assistance and real economic growth in Pakistan. They employed ARDL methodology for analysis.…”
Section: Empirical Literaturementioning
confidence: 93%
“…In her book titled, "Dead aid" she argues that foreign aid does not progress economic growth, but instead tends to promote rentseeking and on many occasions, serves the interest of the elite instead of the overall economy (Moyo, 2009). Synchronously to the assertion of Moyo, a study by Tariq, and Ali, (2019), found a negative relationship between official development assistance and real economic growth in Pakistan. They employed ARDL methodology for analysis.…”
Section: Empirical Literaturementioning
confidence: 93%